Analisis Persepsi Mahasiswa FEBI UINSU Mengenai Mobile Banking Bank Syariah Di Indonesia - Nurhaliza Nurhaliza; Muhammad Irsyad Fadhil; Deri Kurniawan; Nurbaiti Nurbaiti (Pusat Riset dan Inovasi Nasional, 2024)
This research investigates the perceptions of students from the Faculty of Islamic Economics and Business at the State Islamic University of North Sumatra (FEBI UINSU) regarding mobile banking in Indonesian Shariah banks. Data was gathered through a survey conducted among students majoring in Shariah Banking and Management. The findings reveal a predominant positive perception among the majority of students toward mobile banking in Shariah banks. They view it as an effective tool for managing financial transactions, emphasizing a high level of security. Furthermore, students acknowledge the convenience of accessing information related to Shariah banking. The study not only sheds light on students' preferences for Shariah mobile banking services but also provides practical implications for Shariah banks to enhance their services. Recognizing and aligning with these positive perceptions can significantly contribute to the improvement of Shariah-compliant banking services. In essence, the study underscores the importance of understanding student perspectives in shaping and refining mobile banking services in the context of Shariah-compliant banking.